Tunku: prince of peace word and pictures of the Tunku - Lim, Robert (MPH, 2012)
In remembrance of Tunku Abdul Rahman Putra Al-Haj as the 'Father of Independence' and the 'Prince of Peace', this tributary volume combines a treasured collection of Tunku's photographs and his quotes, gleaned from the national archives and past copies of newspapers. These photographs, some of them dating from the 1940s and extremely rare, were lovingly restored for clarity so that we may always remember the story of our nation's past.